Effectiveness of topical budesonide in preventing esophageal strictures after endoscopic resection of esophageal cancer - van de Ven, Steffi Elisabeth Maria; Snijders, Manon J.B.L.; Bruno, Marco J.; Koch, Arjun Dave (Endoscopy International Open, 2020)
Background and study aims A disadvantage of endoscopic resection (ER) of early esophageal cancer (EC) is the high stricture rate after resection. A risk factor for stricture development is a mucosal defect after ER of ≥ 75 % of the esophageal circumference. Stricture rates up to 94 % have been reported in these patients. The aim of this study was to investigate the effectiveness of oral treatment with topical budesonide for stricture prevention after ER of early EC.Patients and methods We performed a retrospective analysis of a prospective cohort study of patients who received topical budesonide after ER of EC between March 2015 and April 2020. The primary endpoint was the esophageal stricture rate after ER. Stricture rates of our cohort were compared with stricture rates of control groups in the literature.Results In total, 42 patients were treated with ER and topical budesonide. A total of 18 of 42 patients (44.9 %) developed a stricture. The pooled stricture rate of control groups in the literature was 75.3 % (95 % CI 68.8 %-81.9 %). Control groups consisted of patients with esophageal squamous cell carcinoma with a mucosal defect after ER of ≥ 75 % of the esophageal circumference. Comparable patients of our cohort had a lower stricture rate (47.8 % vs. 75.3 %, P = 0.007).Conclusions Topical budesonide therapy after ER for EC seems to be a safe and effective method in preventing strictures. The stricture rate after budesonide treatment is lower compared to the stricture rate of patients who did not receive a preventive treatment after ER reported in the literature.